Enraizamento de estacas, sistemas de poda e seleção de cultivares de amoreiras e framboeseiras para regiões subtropicais - Campagnolo, Marcelo Angelo (2012)
In the first chapter, the objective of the present research was to quantify the rizogenic potential of stems and root cuttings of blackberry cultivars, collected in different times, cold storage and treated with indolbutyric acid. In the first experiment, roots and stems cuttings of Tupy blackberry were collected close to it hibernal prune and accomplished in the following times: 07/06, 22/06, 08/07, 22/07, 06/08 and 20/08 of 2009. Already in the second experiment, half of the stems and roots cuttings of Tupy blackberry were submitted to cold storage for 30 days and the other amount of cuttings were placed directly for rooting. The whole cuttings were treated with different concentrations of indolbutyric acid (IBA): 0, 1000, 2000, 3000 and 4000mg L-1 for 10 seconds. In the third experiment, roots cuttings of Choctaw , Ébano , Guarani , Arapaho , Brazos , Cherokee , Comanche , Caingangue , Tupy and Xavante blackberry cultivars. It can be concluded that the roots cuttings presents better results, owing cold storage and without IBA, but there is difference of propagation potential among blackberry cultivars. In the second chapter, the objective of the present work was to quantify the production of cultivars of black and redberry trees in the West region of Paraná. The experimental design was in randomized blocks with four blocks and twelve treatments (cultivars of blackberry trees Arapaho , Xavante , Ébano , Comanche , Caingangue , Choctaw , Tupy , Guarani , Brazos , Cherokee and the redberry tree). Brazos presented the highest yield estimated. The Brazos, Guarani and Tupy cultivars enabled the production of higher mass fruits, that is, Tupy presented good balance between the soluble solids and acidity. The red currant tree presented a high fruit yield. In the third chapter, the objective of this study was to quantify the production of raspberry cultivars in western Paraná. The study was conducted in the Marechal Cândido Rondon, PR. The experimental design was randomized blocks with four blocks and seven treatments (red raspberry cultivars Heritage , Autumn Bliss , Batum , Polana , the yellow raspberry Fall Gold , the black raspberry and hybrid between raspberry and blackberry Boysenberry ). The raspberry Rubus idaeus not adapted to the climatic conditions of West Paraná. On the other hand, the black raspberry is demonstrated excellent option for cultivation with high productivity and quality of its fruit. In the fourth chapter, the objective of this research was to evaluate the pruning time effects at season production of Tupy blackberry. The experimental design was randomized blocks with four blocks and six treatments (pruning time by fifteen days during the winter pruning). Pruning made in early July are the most suitable and late pruning can harm the productive performance of blackberry Tupy in western Paraná. In the fifth chapter, the objective of this study was to investigate the adoption of different pruning as an alternative for production of blackberries in the subtropics areas in Brazil. The experimental design was a randomized block with eight blocks and three treatments (conventional pruning, summer pruning drastic and drastic pruning in winter). The drastic pruning summer facilitates the conduct of blackberry, providing an alternative for the production of blackberries in the subtropics areas